A clinical study of reliability of fine needle aspiration cytology as a diagnostic tool in cervical lymphadenopathy - Krishnaswamy, Jawahar; Rahaman, Khalilur; S., Reshma (International Surgery Journal, 2017)
Background: Cervical lymphadenopathy is one of the commonest presentations in inflammatory and neoplastic disorders. Fine needle aspiration cytology (FNAC) is a well-established diagnostic method used to sample swellings at various sites in the body. It is a simple, quick, inexpensive and minimally invasive OPD technique used for establishing the etiology of cervical lymphadenopathy. Aim of this study was to evaluate the diagnostic accuracy of Fine needle aspiration cytology (FNAC) in cervical lymphadenopathy. Methods: This study included 50 patients presenting to the surgery outpatient department with cervical lymphadenopathy. Detailed history and physical examination was done followed by FNAC in all the patients. The diagnosis was then compared with the gold standard excisional biopsy and histopathological examination by standard statistical methods. Results: Among the 50 patients studied 31 were male and 19 were female. According to histopathologic diagnoses in 50 cases, the patients were diagnosed to have benign lesion in 28 cases (56%), and malignant lesion in 22 cases (44%). Among the benign etiologies, tuberculosis was the most frequent (40%) followed by reactive nonspecific inflammation (16%). Among the malignant etiologies, metastatic deposits constituted 30 % followed by lymphoma constituting 14%. FNAC results supported a benign lesion in 27 cases and were compatible with a malignant lesion in 19 cases. Comparing FNAC results with histopathological diagnoses revealed that, in 46 cases the FNAC results were compatible with histopathology, a total accuracy of 92%. In one case, benign lesion was over diagnosed as malignant and in 3 cases malignant lesions were underdiagnosed as benign lesions. It was found that, in diagnosing benign and malignant lesions, FNAC had a sensitivity of 96.42% and a specificity of 86.36%. Positive predictive value was 90% and negative predictive value was 95%. Out of the 50 patients studied, 20 patients (40%) were confirmed to have tuberculous lymphadenitis by histopathological examination. FNAC supported a tuberculous etiology in 14 cases and 6 cases were underdiagnosed by FNAC. The sensitivity of FNAC in diagnosing tuberculous etiology was found to be 70%, specificity was 100%, positive predictive value was 100%, negative predictive value was 85.71%. Overall the sensitivity of FNAC in diagnosing a pathological cervical lymph node was found to be 92.85%, specificity was 87.5%, positive predictive value was 97.5%, negative predictive value of 70%. Conclusions: The utility of fine needle aspiration cytology in the evaluation of cervical lymphadenopathy has been well established by this study. It is a reliable and convenient method with minimal complications in the management of patients presenting with cervical lymphadenopathy. The various causes of cervical lymphadenopathy were found to be tuberculosis, secondary metastasis, primary malignancy of the lymph nodes and nonspecific reactive lymphadenitis. This study also supports the fact that tuberculosis is still a common cause of cervical lymphadenopathy in India.